THE RELATIONSHIP BETWEEN FLUIDS RESTRICION COMPLIANCE AND INTERDIALYTIC WEIGHT GAIN (IDWG) IN CKD PATIENTS ON REGULER HD IN HEMODIALYSYS ROOM - Nuril Chofifah Ardwina Fatah; Rif'atul Fani (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2026)
Background: Interdialytic Weight Gain (IDWG) is an important indicator of fluid management in patients with chronic kidney disease (CKD) undergoing hemodialysis. Poor fluid restriction adherence may contribute to excessive fluid accumulation and complications. Purpose: This study aimed to examine the association between fluid restriction adherence and IDWG among patients with CKD undergoing regular hemodialysis at Husada Utama Hospital, Surabaya, Indonesia. Methods: This cross-sectional study included 30 patients recruited using total sampling. Fluid restriction adherence was assessed using the End-Stage Renal Disease Adherence Questionnaire (ESRD-AQ), while IDWG was determined from body weight measurements between consecutive hemodialysis sessions. The association was analyzed using Fisher’s exact test with statistical significance set at p < 0.05. Results: Most participants were aged ≥46 years (76.7%) and had undergone hemodialysis for more than 12 months (90.0%). Overall, 76.7% adhered to fluid restriction and had normal IDWG. All adherent participants had normal IDWG, whereas all non-adherent participants had high IDWG. A significant association was observed between fluid restriction adherence and IDWG (p < 0.001). Conclusion: Fluid restriction adherence was significantly associated with IDWG, highlighting the importance of supporting adherence as part of fluid management in hemodialysis care.